Cassava breeding in Nigeria adapts tricot on-farm testing to achieve inclusive breeding - International Institute of Tropical Agriculture; Teeken, B. (IITA Communication Office, 2024)
Discover the innovative cassava breeding collaboration between IITA and NRCRI in Nigeria in this documentary. See how they've enhanced the tricot method for inclusivity, especially in social and gender aspects. The film showcases their partnership with the variety release committee to pilot tricot for on-farm testing, gathering valuable insights on crop preferences considering regional, climate, and social/gender differences. Learn how tricot empowers crop users, involving them in the breeding process, and acts as a learning and knowledge-sharing platform.